Phosphine Oxide Additives for High‐Brightness Inorganic Perovskite Light‐Emitting Diodes. Issue 3 (21st November 2021) - Schmidt, Ines; Olthof, Selina; Xu, Hui; Meerholz, Klaus
Abstract: In the search for cost‐efficient, simple, and solution processable light‐emitting diodes, metal halide perovskites show encouraging developments. In particular, the purely inorganic CsPbBr3 is a promising material with outstanding optoelectronic properties. However, the poor solubility of Cs‐salts leads to discontinuous film formation and a high density of defect states at the crystal surface. These problems are known to be reduced by Lewis base additives. In this work, a facile fabrication method using phosphine oxide ligands such as the trioctyl and triphenyl derivatives (TOPO and TPPO, respectively) is introduced. These additives reduce surface defect states, lead to an energetic confinement of charge carriers, and improve radiative recombination in the perovskite crystals. Using X‐ray diffraction, changes in crystallinity are observed, in particular the crystallinity of the 3D phase CsPbBr3 is reduced by addition of TOPO, while changes to the 0D phase (Cs4 PbBr6 ) are much smaller. Overall, TOPO and TPPO containing films result in current efficiencies as high as 14 and 10 cd A −1 and an outstanding brightness of more than 57 800 and 18 300 cd m −2 in a relatively simple device stack. Abstract : A simple preparation procedure for CsPbBr3 ‐based perovskite light‐emitting diodes with improved efficiency using phosphine oxide ligands such as the trioctyl and triphenyl derivatives (TOPO and TPPO) is presented. A significant increase in current efficiency and brightness is achieved, which is attributed to increased charge confinement as well as an effective surface defect state passivation introduced by the additive.